Enhancing Family Resilience through Legal Understanding and Education - Junaidah Junaidah; Deswinta Deswinta; Karinta Rengganingtiyas; Linda Iqwaningsih; Mirna Wati; Lais Batrisiya (Al-Qalam Institute, 2025)
This study aims to analyze the contribution of legal understanding and education to family resilience in the Kelurahan Jagabaya III community, Bandar Lampung. Family resilience is crucial for social stability, particularly in the face of globalization and rapid societal changes, with legal and educational factors playing a significant role in strengthening family dynamics. The research uses a descriptive qualitative approach supported by action research, collecting primary data through field observations, interviews, and documentation of intervention activities. The study finds that family resilience is a dynamic process influenced by internal and external factors such as legal knowledge and education. Families with higher legal literacy experience fewer conflicts and stronger relationships, while education enhances family problem-solving and adaptability. The integration of legal education within family dynamics shows positive outcomes, with community-based programs significantly improving resilience. Furthermore, the research emphasizes the need for educational interventions and legal literacy programs to strengthen families. This study contributes to the understanding of family resilience by highlighting the interplay between legal knowledge and education in fostering stability.